ZONING EVALUATION IN THE KARST CAMPURDARAT OF TULUNGAGUNG DISTRICT - Ratri Juang Megarismi (Kalyanamitra: Journal of Archaeological Resource Management, 2025)
Zoning is an important part of preservation, but sometimes the process is not in accordance with Undang-undang No. 11 Tahun 2010 on Culture Heritage. In Wajak Cave and Song Gentong Cave, zoning studies still need to be evaluated, especially at this time there are several problems that occur in the two caves. So the analysis used is zoning analysis, policy analysis, and SWOT analysis of zoning aspects. So that the recommendations that can be given after the analysis are the establishment of the Wajak Cave and Song Gentong Cave Cultural Heritage along with the zoning determination, the intervention of related policy makers, increasing public awareness of the caves, and overcoming marble mining in the area.